2021
DOI: 10.1080/1331677x.2021.1919542
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of covid-19 pandemic on agriculture: systematic literature review in the frameworks of vulnerability, resilience and risks involved

Abstract: Covid-19 pandemic provided many negative effects on world economies and people around the world. The covid-19 creates many threats to sustainability of agriculture sector which is very sensitive because of food supply security needs. First of all, it is necessary to analyse and comprehend the immediate consequences of current pandemic on agricultural and food systems in order to develop necessary actions. The risks, vulnerability, resilience and systemic shifts of agricultural systems need to be better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 79 publications
1
42
0
3
Order By: Relevance
“…However, the collective actions have been taken by various countries for surplus food production and cold storages. This will help those countries who are dependent on others for their food supply [62]. Undoubtedly, the pandemic greatly affected the economy and led to income reductions.…”
Section: Agriculturementioning
confidence: 99%
“…However, the collective actions have been taken by various countries for surplus food production and cold storages. This will help those countries who are dependent on others for their food supply [62]. Undoubtedly, the pandemic greatly affected the economy and led to income reductions.…”
Section: Agriculturementioning
confidence: 99%
“…A study in the US found that the farmers were at higher risk of contracting COVID-19 ( 38 ). This has led to a reduction in farm produce across the world ( 39 , 40 ). This is difficult to ascertain in Bhutan due to a lack of data.…”
Section: Discussionmentioning
confidence: 99%
“…Our quantitative study results are similar to earlier qualitative study results on COVID-19. In some early studies, Štreimikien ė et al [20] found that the pandemic hindered the development of agriculture. Due to the decline in purchasing power and the restrictions on people going out by the epidemic prevention policy, people's food safety and security have been significantly weakened.…”
Section: Discussionmentioning
confidence: 99%
“…First, we are trying to understand the specific impact of COVID-19 on agricultural food sales in order to find a way for agricultural enterprises and authorities to cope with this dilemma. At present, the quantitative research on the impact of the COVID-19 pandemic on the sales of agri-food products and the revenue of agri-food enterprises is relatively limited, mainly focusing on some non-quantitative studies [17][18][19][20]. This study is based on the 2015-2020 data of listed Chinese agri-food companies, quantitatively estimates the impact of the pandemic through industrial econometrics and fills the gaps in the literature.…”
Section: Introductionmentioning
confidence: 99%